2020
DOI: 10.1186/s12875-020-01336-1
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth consultations in general practice during a pandemic lockdown: survey and interviews on patient experiences and preferences

Abstract: Background During the first COVID-19 pandemic ‘lockdown’ in Aotearoa/New Zealand (March–May 2020, in which strict ‘stay at home’ measures were introduced), general practices were advised to use telephone and video consultations (telehealth) wherever possible instead of the usual in-person visits. This was a sudden change for most practices and patients. This research aimed to explore how patients accessed general practice during lockdown and evaluate their experiences with telehealth, to inform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
241
2
43

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(307 citation statements)
references
References 25 publications
21
241
2
43
Order By: Relevance
“…We did not seek information about reasons for choice of consultation method in this study, but personal circumstances, familiarity/existing relationships with service providers, and perceived convenience are likely factors driving choice of method. 8 Hesitancy to use video consultations for sexual healthcare (and healthcare in general) has been associated with fears about confidentiality and security in previous research. 20 21 It has been suggested that despite being avid mobile phone users, many young people are not comfortable making or taking calls, 22 which could partly explain the lack of support for telephone consultations.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We did not seek information about reasons for choice of consultation method in this study, but personal circumstances, familiarity/existing relationships with service providers, and perceived convenience are likely factors driving choice of method. 8 Hesitancy to use video consultations for sexual healthcare (and healthcare in general) has been associated with fears about confidentiality and security in previous research. 20 21 It has been suggested that despite being avid mobile phone users, many young people are not comfortable making or taking calls, 22 which could partly explain the lack of support for telephone consultations.…”
Section: Discussionmentioning
confidence: 90%
“…4 5 'In-person' consultations were reserved for limited numbers of patients and conditions as determined by telephone triage, and consultations were conducted by telephone, video and messaging applications (telehealth or telemedicine). 4 6 7 Researchers have already explored patient experiences of primary healthcare delivered by telehealth during lockdown in New Zealand, 8 but the extent to which telehealth is appropriate for, and was used for, sexual and reproductive health (SRH) issues is unclear. SRH consultations often involve discussion of confidential, sensitive issues.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the establishment of primary care or the initial consultation, similar to a first date, may not be welcomed by all and could negatively affect patient experience or the development of a sense of "my doctor." A survey of primary care patients during the pandemic found that telehealth was considered the most appropriate in the presence of a pre-existing clinical relationship [21]. An analysis of 620 patient satisfaction survey outcomes from clinic encounters found that new visit type was associated with lower patient satisfaction (parameter estimate -0.75; 95% CI -1.00 to -0.049) [22].…”
Section: Unintended Consequences Of Telehealthmentioning
confidence: 99%
“…Offering the option of phone or zoom interviews may be helpful for youth participants, particularly in light of COVID-19 changes. 41 In this study undertaken in 2019 (pre COVID-19), phone interviews appear to yield comparable data and may be a good option for some young people. 42 This study shows that even in an intentionally youth-friendly practice, barriers exist in offering an accessible, acceptable, equitable, appropriate, effective safe consulting environment.…”
Section: Discussionmentioning
confidence: 80%